Optimization and characterization of oil palm empty fruit bunch fermentation for cellulase production by Botryosphaeria rhodina UPM3 - Kamal Bahrin, Ezyana (2012)
Malaysia is well positioned as the major producers and exporters for palm oil industry worldwide. Hence, oil palm industry is currently producing the largest amount of biomass in Malaysia. In line with the Malaysian government approach to maximize the use of all by-products and waste streams, oil palm empty fruit bunch (OPEFB) is one of potential feedstock for industrial scale since it is abundant and available throughout the year. Integration of ‘Waste to Wealth’ concept is applicable to the palm oil industry in order reduce all production costs. Value added of oil palm solid waste into useful products such as organic acid, sugars, compost, biogas and enzymes may overcome the waste disposal problem in the mill. Locally isolated fungus, namely Botryosphaeria rhodina UPM3 was found to be the best cellulase producing fungus among six fungi using rapid screening method. Solid state fermentation (SSF) is a strategic approach for ioconversion of lignocellulosic material by filamentous fungus. Results suggested that FPase (2.84 U/g) and CMCase (7.19 U/g) activities reached maximum production on day 3 of SSF. While β-glucosidase (0.09 U/g) indicated high activity on day 6 of SSF. Maximum FPase activity was obtained at the optimum levels of SSF parameters (fungal agar plug, 30°C incubation temperature,20% initial moisture content, 5.0 g of substrate, initial pH of nutrient at 7.0 and without mixing). The OPEFB particle size of 0.42-0.60 mm contributed to the maximum activity of FPase and β-glucosidase whereas CMCase activity was maximized when 0.84-1.00 mm particle size was used in SSF. High cellulase production at low moisture content (20%) is a very rare condition for fungi cultured in SSF but B. rhodina UPM3 was capable to tolerate this condition and give a great advantage for large scale production. Response surface method was applied in this study to improve the cellulase production from OPEFB by B. rhodina UPM3. An experimental design based on two-level factorial was employed to screen the significant environmental factors for cellulase production. From the analysis of variance (ANOVA), initial moisture content, amount of substrate and initial pH of nutrient supplied in the SSF system were significantly influenced the cellulase production. Then, the optimization of the variables was preceded in Central Composite Design (CCD). B. rhodina UPM3 exhibited its best performance with a high predicted value of FPase enzyme production (17.95 U/g) when the initial moisture content was 24.32%, initial pH of nutrient was 5.96 and 3.98 g of substrate. The statistical optimization from actual experiment resulted in a significant increment of FPase production from 3.26 to 16.83 U/g (5.16-fold). The model and design on the optimization of the environmental factors in this study was dependable to predict the cellulase production by B. rhodina UPM3. The enzyme productions under optimized condition of SSF were as follows: FPase (18.48 U/g), CMCase (20.54 U/g), xylanase (22.00 U/g) and β-glucosidase (1.13 U/g). In addition, fermented OPEFB by B. rhodina UPM3 was also analyzed and characterized to have a better understanding towards the macroscopic observation in SSF system. SEM micrographs showed a remarkable fungal growth cultivated on OPEFB for day 5 and 7. The craters of OPEFB provide a good anchorage for B. rhodina UPM3 mycelia to attach on the substrate. Cellulose (7.78%) and hemicellulose (22.6%) composition were gradually declined throughout the fermentation period. However, lignin content resided in the OPEFB fiber was remaining unchanged until the end of the fermentation. This finding suggested that B. rhodina UPM3 was unable to decompose lignin in a short period of time. Degradation of intra- and inter-linkage within lignocellulosic component in OPEFB indicated a vital finding of B. rhodina UPM3 capability to decompose these materials during SSF. Overall, OPEFB is one of promising lignocellulosic feedstock and can be employed as substrate in SSF by locally isolated fungus, B. rhodina UPM3 in order to produce cellulase enzymes.